Pengembangan Pendidikan Pancasila Dan Kewarganegaraan Melalui Kepala Bernomor Terstruktur Sebagai Model Pendidikan Kecakapan Kewarganegaraan - Slam, Zaenul (University of Muhammadiyah Malang, 2024)
Students' citizenship skills are low as a result of the learning model because the lecturers are monotonous in lectures with occasional questions and answers and discussions. This model makes passive learning, saturating and boring students. Ideally learning activates students more and is full of meaning, so to overcome these problems the development of PCE is carried out through structured numbered heads as a model for student citizenship skills education. This study aims to describe the development of PCE with structured numbered heads as a model of citizenship skills education. This research is based on a qualitative approach with a case study method. The results of his research, with the development of PCE through structured numbered heads are able to educate citizenship skills for PGMI students. It is recommended to optimize the development of PCE through structured numbered heads as a model for civic skills education for students of various levels of education.